Automated modeling of shaft leading elements in the rear axle gear - Matarneh, Rami; Sotnik, Svitlana; Belova, Nataliya; Lyashenko, Vyacheslav (International Journal of Engineering and Technology, 2018)
The aim of this work is to automate the design process of the "shaft leading" of the rear axle gear in order to reduce the time and effort. All the technical requirements for the design process are given and SolidWorks development medium is selected. A 3D model was developed and steel material 40X was added and its parameters were specified. A finite element analysis of the created design performed under the action of the torque transmission force.Â Â